2003
DOI: 10.1007/s00220-003-0947-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Trace Superpotentials vs. Matrix Models

Abstract: We consider N = 1 supersymmetric U(N) field theories in four dimensions with adjoint chiral matter and a multi-trace tree-level superpotential. We show that the computation of the effective action as a function of the glueball superfield localizes to computing matrix integrals. Unlike the single-trace case, holomorphy and symmetries do not forbid non-planar contributions. Nevertheless, only a special subset of the planar diagrams contributes to the exact result. Some of the data of this subset can be computed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…According to the field theory analysis in [5][6][7], because fields M are gauge singlets, we should leave M untouched at the level of free energy and add them back to the effective action directly by the prescription (1.1). This point has also been emphasized in [18,19]. Using this new understanding, we redo the integration of magnetic matrix model in [16,17] at Appendix to show the consistence.…”
Section: The Seiberg Dual Theory Of U(n C ) Groupmentioning
confidence: 80%
See 1 more Smart Citation
“…According to the field theory analysis in [5][6][7], because fields M are gauge singlets, we should leave M untouched at the level of free energy and add them back to the effective action directly by the prescription (1.1). This point has also been emphasized in [18,19]. Using this new understanding, we redo the integration of magnetic matrix model in [16,17] at Appendix to show the consistence.…”
Section: The Seiberg Dual Theory Of U(n C ) Groupmentioning
confidence: 80%
“…The baryonic deformation has been addressed in [21][22][23][24] where it has been shown that although the baryonic deformation makes the boundary condition in matrix models very tricky, there is a way to sum up relative contributions for field theory in matrix model expansions. The multi-trace deformation was investigated in [18,32] where it was pointed out [18] that the direct integration in the multi-trace matrix model does not give back correct results in field theory. But by linearization we can reduce the multi-trace matrix model to the single-trace matrix model, thus the standard result can be applied.…”
Section: Introductionmentioning
confidence: 98%
“…The example given in Appendix A should help to clarify this. We should emphasize that the above procedure must by done diagram by diagram -there is no obvious way to directly relate the entire glueball superpotential to the matrix model free energy; the situation is similar to [11] in this respect.…”
Section: Rpmentioning
confidence: 99%
“…There the explicit factorization of curves without matter of [19] was known. Factorization properties were also used in the context of SO(N c ) theories [20] and multi-trace operators [21] to obtain the appropriate effective superpotentials W ef f (S).…”
Section: Introductionmentioning
confidence: 99%